The influence of maternal HIV and ART exposure on neonate brain white matter integrity and organisation - Magondo, Ndivhuwo (Department of Human Biology, 2023)
Improved legislation and widespread access to treatment has led to a new cohort of children who have in utero exposure to maternal HIV, but remain HIV negative through the use of antiretroviral therapy (ART), known as HIV exposed-uninfected (HEU) children. While HEU infants and children are healthier than their infected peers, they experience some developmental delays as compared to uninfected unexposed populations. Few brain imaging studies have been done in HEU infants and children, and so the effects of the exposure to in utero HIV and ARVs on their neurodevelopment are not well understood. As this population matures, there is a need for studies to determine how HIV as well as ART exposure in utero and at birth affect white matter (WM) structure and its connectivity. This study used diffusion tensor imaging (DTI) tractography and graph theory to examine the possible influence of HIV and ART exposure in utero on neonate WM integrity (as measured by DTI parameters) and organisation (evaluated with graph theory measures). We hypothesised that HIV exposure will alter WM integrity, however structural organisation will remain unchanged across groups. We investigated HIV exposure and ART duration group differences in fractional anisotropy (FA) and mean diffusivity (MD) of the WM connections in the brain, as well as graph measures including strength, local efficiency, nodal efficiency, global efficiency, transitivity, and modularity. To examine these differences, a linear regression analysis was performed between the groups while correcting for maternal weight gained per week of pregnancy and maternal education. The study found that, regardless of when ART is started by the mothers, certain regions and tracts in the brain are seemingly influenced by HIV exposure. Infants whose mothers have been on ART pre-conception have higher MD values than their unexposed and uninfected peers, while those who have been exposed to ART postconception were shown to have lower FA values than their unexposed and uninfected counterparts. These results imply that ART duration influences WM integrity and may be neuroprotective for FA, which is more related to WM integrity, but not for MD, which relates to WM organisation. ARV exposure duration and CD4 count are shown to be positively associated with FA tracts, while CD4 count is negatively associated with MD. This relationship highlights the potential impact of maternal immune health on fetal brain development. While there are structural differences in certain WM tracts, the overall structural organisation remains unchanged, as no graph theory measures yielded significant results besides nodal efficiency. The brain's dense connective network may bridge gaps from damage in specific tracts throughout the connectome.